Container barge (un)reliability in seaports: a company case study at the port of Antwerp. (18th October 2021) - Oganesian, Virzhiniia; Sys, Christa; Vanelslander, Thierry; Hassel, Edwin Van
Inland waterways and ports play an important role in the entire transport system in the Hamburg-Le Havre range, and for the seaports of Antwerp and Rotterdam in particular. The high proportion of inland navigation for both ports can be explained by reasons such as an extensive network along with a safe, reliable, sustainable and cost efficient transport. However, despite all these advantages, container barge transportation still faces certain challenges. A major challenge relates to the unreliability of barge handling in large seaports, affecting overall performance of barge services essentially. This research shows that barge congestion exists, and it examines the causes of the observed phenomena. Next, it also provides an overview of solutions that are being developed in the port of Antwerp to improve and optimise container barge handling. Last, a case study is developed for a company that is located in the near proximity of the port of Antwerp, where the impact of barge handling unreliability is analysed.